Hubungan Self-Esteem dengan Perilaku Bullying pada Remaja - Oktaviana, Berliana; Ahmad, Ghulam; Waluya, Ady (Jurnal Pengabdian Ilmu Kesehatan, 2026)
Bullying behaviour in teenagers is one of the social problems that can have a negative impact on mental health and psychosocial development. One of the factors related to bullying behaviour is self-esteem. This research aims to analyse the relationship between self-esteem and bullying behaviour in teenagers. The research method used is quantitative method with cross-sectional design. The population in this study is students in class X and XI which totalled 926 students with a sample of 280 respondents who were selected using the Proportional Stratified Random Sampling technique. Data collection was carried out using the Rosenberg Self-Esteem Scale (RSE) questionnaire and the Olweus Bully/Victim Questionnaire (OBVQ) questionnaire. Data analysis method using phi correlation test. The results of this study show that there is a significant relationship between self-esteem and bullying behaviour in teenagers with a p-value of 0.000 (<0,05), teenagers with low self-esteem levels tend to be more at risk of bullying behaviour compared to teenagers who have high self-esteem levels.